Review on Chloroxylon swietenia DC: An IUCN Red Listed Native, Timber-Yielding and Pharmaceutically Useful Tree Species in Dry Lands of India - Archana, R.; Sivakumar, V. (Indian Forester, 2024)
Chloroxylon swietenia is a potential drought-tolerant tree species for increasing the vegetation of dry lands in India. The natural populations of the species are distributed from central India to south India. This tree has to be domesticated to increase the availability of secondary timber-yielding species. This species has manifold utilities viz., used for preparing farming tools, house construction and interior designs. Wood has an aroma which is rich in essential oils and yields an attractive wood of excellent qualities. Leaves are also used in the preparation of various phytopharmaceutical-based products for curing several ailments. The stem bark has been used in many ethnobotanical formulations for curing skin diseases. It is also may be recommended for agroforestry systems to increase the diversity of cropping systems of farmers. Therefore, this tree species should be given importance in bringing under human interventions for exploiting the multiple utilities needful to the farming community of India.